Ефектите на стереотипизацијата во бугарската книжевност од деветнаесетиот век (во драмата „Криворазбраната цивилизација“ на Добри Војников и поемата „Изворот на белоногата“ на Петко Славејков) - Трајче Стамески (Бугарија – Македонија – Словенија: Меѓукултурни дијалози во XXI век. (Рецензирана колективна научна монографија), „Аз-буки“ Софија 2019, 2019)
This article focuses on two extremely important works in the Bulgarian literature from the 19th century. It analysis them from the perspective of the importance of stereotyping (auto imaging or imaging of the other) for the national identity, its influence on identity issues and dilemmas, as well as its contribution in the representation of the wider image about the culture of the Bulgarian society in comparison with other cultures.
Keywords: Stereotype, culture, identity, tradition, society